Millimeter-Wave Low Noise Amplifiers - Božanić, Mladen (Signals and Communication Technology,, 2018)
This book examines the challenges of low-noise amplifier (LNA) research and design in the millimeter-wave regime by dissecting the common LNA configurations and typical specifications into parts, which are then optimized separately over several chapters to suggest improvements in the current designs. Current trends towards increased wireless connectivity and the need to stay connected everywhere and all the time, call for extremely high data rates. Most of the wireless networks operate in frequency bands measured in low gigahertz. Typically, this is done through channels with moderate bandwidth. To keep up with the trends for increased data transmission rates, new and innovative ideas are needed. One of the areas of investigation is the transmission in millimeter-wave regime, ranging from 30 GHz to 300 GHz, where there is an abundance of bandwidth. The low-noise amplifier (LNA) is the first component that appears in the front ends of most microwave and millimeter-wave receivers after an antenna. The performance of a millimeter-wave receiver is therefore largely dependent on the performance of the LNA that is used. Primarily, the LNA is tasked with amplifying a signal while introducing as little noise into the signal as possible. This is a necessity, because the signal received by the antenna is already submerged in noise, thus the signal, before it can be processed, needs to be amplified with the smallest possible amount of additional noise introduced in this process. This is even more so true, due to the limitation of the wave propagation in millimeter-wave regime, where there is a trade-off between data-rate, range and power.